2007
DOI: 10.1016/j.yjmcc.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α induced-VEGF overexpression in bone marrow stem cells protects cardiomyocytes against ischemia

Abstract: Hypoxia inducible factor-1α (HIF-1α) is a proangiogenic transcription factor stabilized and activated under hypoxia. It regulates the expression of numerous target genes, including vascular endothelial growth factor (VEGF) and other cytoprotective proteins. In this study, we hypothesized that bone marrow stem cells (BMSCs) secrete growth factors which protect cardiomyocytes via HIF-1α pathway.Methods-BMSCs were obtained from transgenic mice overexpressing green fluorescent protein (GFP). The study was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 43 publications
7
103
1
Order By: Relevance
“…The increase in host CMCs may have been due to the cardioprotective effects of post-QQc by attenuation of myocardial ischemia through angiovasculogenesis. Dai et al [44] reported that VEGF, the expression of which was upregulated in post-QQc in our study, has antiapoptotic effects on CMCs. Transplanted cells post-QQc may secrete cytokines directly, protecting ischemic or apoptotic CMCs.…”
Section: Enhanced Cardiac Repair By Engraftment Of Post-qqc Cellssupporting
confidence: 59%
“…The increase in host CMCs may have been due to the cardioprotective effects of post-QQc by attenuation of myocardial ischemia through angiovasculogenesis. Dai et al [44] reported that VEGF, the expression of which was upregulated in post-QQc in our study, has antiapoptotic effects on CMCs. Transplanted cells post-QQc may secrete cytokines directly, protecting ischemic or apoptotic CMCs.…”
Section: Enhanced Cardiac Repair By Engraftment Of Post-qqc Cellssupporting
confidence: 59%
“…As MDSCs do not appear to contribute directly to cardiomyocyte regeneration through their differentiation into a cardiomyocyte lineage or fusion with existing cardiomyocytes, the likely mechanism for MS-MDSC cardiac recovery is improved angiogenesis, as this has been previously shown to be critical for cardiac repair after injury and disease. 18,41 To support our in vivo results, we explored MDSC behavior in vitro under a variety of conditions. We observed an increased secretion of VEGF after mechanical stimulation, which may partially explain the improvement in MS MDSC engraftment and repair and further supports our earlier results.…”
Section: Discussionmentioning
confidence: 84%
“…In addition to Akt signal transduction, many investigators work with hypoxia inducible factor 1 alpha (HIF-1α) and Pim-1 kinase. HIF-1 alpha HIF-1 alpha is a pro-angiogenic transcription factor which regulates the expression of many genes such as vascular endothelial growth factor (VEGF), angiopoietin 1 (ANGPT1) and ANGPT2, placental growth factor (PGF), and platelet-derived growth factor B (PDGFB) (Dai et al, 2007;Manalo et al, 2005). Under hypoxic conditions, hydroxyl reaction does not occur, causing HIF-1 protein to escape from inhibition and be activated, resulting in transcription of many genes and stimulates angiogenesis (Pugh and Ratcliffe, 2003).…”
Section: Gene Transfection Aktmentioning
confidence: 99%
“…Under hypoxic conditions, hydroxyl reaction does not occur, causing HIF-1 protein to escape from inhibition and be activated, resulting in transcription of many genes and stimulates angiogenesis (Pugh and Ratcliffe, 2003). Basing on the important function of HIF 1 in hypoxic cells, it's expression was introduced in MSCs, which was expected that these MSCs could protect co-culture cardiomyocytes through HIF pathway (Dai et al, 2007).…”
Section: Gene Transfection Aktmentioning
confidence: 99%